Therapeutic alliance in face-to-face versus videoconferenced psychotherapy - Rees, Clare; Stone, Sheona (American Psychological Association, 2005)
Despite the great potential videoconferencing holds for providing psychotherapy services to a wide range of individuals, it is presently underused by psychologists. Do psychologists hold negative attitudes that interfere with their willingness to use the technology? What do psychologists think about the impact of the technology on the therapeutic alliance? Thirty clinical psychologists were randomly assigned to watch an identical therapy session, either face-to-face or videoconferencing format. Our prediction that psychologists in the videoconferencing condition would rate the therapeutic alliance significantly lower than would psychologists in the face-to-face condition was supported. We discuss the need to develop appropriate therapist training and improve the general dissemination of information regarding videoconferencing as an important means by which to reduce negative attitudes toward the technology.